Speaking skills development in ESL E-learning educational environment - Safin Ildar Khamzovich; Khasanova Oxana Vladimorovna; Karimova Anna Anatolyevna; Semushina Elena Yurievna; Shustova Svetlana Viktorovna (Revista on line de Política e Gestão Educacional)
The article focuses on the peculiarities of teaching speaking in E-learning educational environment, which today is a must for organizing educational process of high quality. The material to analyze is based on the on-line part of the course "Foreign language practice (English)", worked out for the students of Bachelor’s Program "Pedagogical Education (double major) and Second Foreign language " (5 years, full time) of Kazan Federal University. The status of foreign language teachers has always been high as they play an important role in fostering cross-cultural communication, in promoting tolerance and bridging nations and countries. It is up to teachers to make students understand the essence of successful communication that lies in respecting the diversity of cultures, peoples, nations, and languages. In this respect being culturally competent is of great importance (MINGAZOVA; MELLO; GAFIYATOVA, 2017). The course "Foreign language practice (English)" is located on the platform edu.kpfu.ru. Special attention is paid to the implementation of a communicative approach when teaching speaking, considering the individual educational trajectory of the student or the study group. In addition, the research gives the gist of the theoretical analysis and the results of the experimental testing of the teaching speaking approaches, the effectiveness of the methods used when forming speaking skills of the students. Thus, we could state that when teaching speaking in E-learning educational environment, it is necessary to conduct preparatory stages in the form of studying and training new vocabulary online, which leads to the possibility to give more time to group forms of work during face-to-face classes. The groundwork and analysis of the selected factual material indicate that, teaching speaking can be effectively carried out online, if certain requirements are met, such as the use of a communicative approach, the proper organization of individual and group work, high self-discipline and motivation of the student and the teacher. The use of E-learning educational environment can improve the quality of training speaking skills in higher educational institution.